(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In this study, we studied the clinical course of pneumonia in 47 infants of early age with community-acquired pneumonia and various congenital heart defects as comorbidities. The importance of timely pathogenetic complex therapy is shown, including the elimination of circulatory failure, etiotropic antibacterial, cardioprotective drugs.